Cognitive Frailty in China: Results from China Comprehensive Geriatric Assessment Study - Ma, Lina; Zhang, Li; Zhang, Yaxin; Li, Yun; Tang, Zhe; Chan, Piu (Frontiers in Medicine, 2017)
Objective Cognitive frailty (CF) refers to the co-occurrence of physical frailty (PF) and cognitive impairment in persons without dementia. We aimed to explore the prevalence and associated factors of CF in China. Method Data were obtained from the China Comprehensive Geriatric Assessment Study. A total of 5,708 community-dwelling older adults without dementia were included. CF was assessed using the Mini–Mental State Examination for the evaluation of cognitive status and the Comprehensive Geriatric Assessment-Frailty Index for the evaluation of PF. Participants with both cognitive impairment and PF were classified as having CF. Sociodemographic and clinical history was also collected. Logistic analysis was used to explore the association between the associated factors and CF. Results The overall crude prevalence of CF was 3.3% [95% confidence interval (CI) = 3.0–4.0], and the standard prevalence of CF was 2.7% (95% CI = 2.0–3.0). The prevalence of CF was significantly higher in women than men and higher in residents of rural areas than urban areas. Moreover, the prevalence of CF was found to increase with age. Multiple factor analysis showed that depression (OR = 2.462, 95% CI = 1.066–5.687) and hearing impairment (OR = 2.713, 95% CI = 1.114–6.608) were independent associated factors of CF in elderly individuals with PF. Conclusion Our results provide the first empirical evidence of CF in China. We have identified several associated factors with CF which should be considered while assessing older adults. More studies in Chinese population with CF are demanded to confirm with our findings.